Reading–Writing and Math Prerequisites as Predictors of Children’s Transition from Kindergarten to School - Horațiu Catalano; Ion Albulescu; Anca Ani-Rus; Mirela Albulescu; Gabriela Mestic; Ana Rus (Education Sciences)
The transition stage to pre-primary school represents a key event, in which the support received from family and teachers is essential in facilitating the transition and in ensuring an effective adjustment to the school environment. Our study aimed to investigate the impact of mathematical prerequisites on cognitive development, compared to the impact of reading and writing prerequisites, from the perspective of parents and early childhood educators. Thus, we quantified the impact of reading–writing and math prerequisites on children’s transition from kindergarten to school, analyzing the challenges, opportunities, and possibilities that arise. The sample consisted of 685 parents and 188 teachers, using the preschool prerequisites screening standardized questionnaire developed by the company Cognitrom, a questionnaire-survey, and the focus group method. Initially, the fidelity of the research instrument was assessed by calculating Cronbach’s alpha coefficient. The data distribution was tested using the skewness and kurtosis coefficients. Subsequently, descriptive analyses were carried out in order to provide an overview of the data collected by performing a multiple linear regression analysis. In addition, the Phi coefficient and V Cramer’s V coefficient were used to analyze the association between the research variables. By corroborating the obtained results, we can state that, from the parents’ and early childhood teachers’ perspective, math prerequisites have a greater influence on children’s cognitive development in the transition process from kindergarten to school compared to reading–writing prerequisites, confirming the general hypothesis.